Efficient Mixed‐Cation Mixed‐Halide Perovskite Solar Cells by All‐Vacuum Sequential Deposition Using Metal Oxide Electron Transport Layer. Issue 7 (10th May 2019) - Kam, Matthew; Zhu, Yiyi; Zhang, Daquan; Gu, Leilei; Chen, Jiaqi; Fan, Zhiyong
Abstract : The incorporation of various cations and halides to form mixed perovskites has enabled perovskite solar cells (PSCs) to exceed 20% power conversion efficiencies (PCEs). However, they are primarily prepared by solution methods, which limit film uniformity and scalability. Although co‐evaporation is used to prepare all‐vacuum‐deposited PSCs with a decent performance, it involves multiple sources and quartz crystal monitors (QCMs) to simultaneously control deposition rates and film thicknesses, which increase production cost and fabrication complexity and interfere QCMs' reading precision. Herein, a simple and cost‐effective sequential vapor deposition involving only one QCM and two sources is demonstrated as an advantageous and reliable method to fabricate high‐quality and uniform mixed‐cation mixed‐halide perovskite films with microscale grain sizes and extraordinary morphology for the PSC application. In addition, for the first time, radio frequency (RF)‐sputtered SnO2 is implemented into all‐vacuum‐deposited PSCs as an electron transport layer (ETL). Together with evaporated copper phthalocyanine (CuPc) as a thermally and chemically stable low‐cost hole transport layer (HTL), alternative to the commonly used 2, 2′, 7, 7′‐tetrakis( N, N ‐di‐ p ‐methoxyphenylamino)‐9, 9′‐spirobifluorene (Spiro‐OMeTAD), which is costly, highly hygroscopic, and deliquescent, a respectable PCE of 15.14% is achieved with a promising device stability and negligible hysteresis. Abstract : A simple but powerful sequential vapor deposition technique is introduced to fabricate high‐quality mixed‐cation mixed‐halide perovskite films for perovskite solar cells. Using copper phthalocyanine as a hole transport layer and sputtered SnO2 as an unprecedentedly employed electron transport layer in all‐vacuum‐deposited mixed‐perovskite solar cells, high‐performance devices are achieved, envisioning future cost‐effective commercialization.